Current advances in biosampling for therapeutic drug monitoring of psychiatric CNS drugs. (August 2015) - Mercolini, Laura; Saracino, Maria Addolorata; Protti, Michele
Many CNS drugs are effective for the treatment of psychiatric disorders. Psychotropic drugs work differently, thus clinical outcomes for many patients may be insufficient. For this reason it could be useful the measurement of drug levels for clinical decision-making. Analytical goals in therapeutic drug monitoring (TDM) should be established by selecting the appropriate biological matrix. The aim of this review is to highlight the usefulness of TDM for antiepileptics, antidepressants and antipsychotics, with a focus on current advances in biosampling. The literature on TDM was reviewed up to March 2015. An overview on the use of alternative biological matrices is provided to address the current issues and advances in the field of biosampling for psychiatric CNS drug TDM.